2022
DOI: 10.3390/ijms23031216
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruptors and Prostate Cancer

Abstract: The role of endocrine disruptors (EDs) in the human prostate gland is an overlooked issue even though the prostate is essential for male fertility. From experimental models, it is known that EDs can influence several molecular mechanisms involved in prostate homeostasis and diseases, including prostate cancer (PCa), one of the most common cancers in the male, whose onset and progression is characterized by the deregulation of several cellular pathways including androgen receptor (AR) signaling. The prostate gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 143 publications
0
12
0
Order By: Relevance
“…In recent years, technological progress and the development of new methods have largely led to an increased understanding of the underlying molecular mechanisms that promote tumor growth and progression ( 4 ). The advent of current drug and therapy combinations has enriched the treatment options for PCa, providing more treatment options for patients with PCa ( 5 ). However, there are certain challenges for clinical practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, technological progress and the development of new methods have largely led to an increased understanding of the underlying molecular mechanisms that promote tumor growth and progression ( 4 ). The advent of current drug and therapy combinations has enriched the treatment options for PCa, providing more treatment options for patients with PCa ( 5 ). However, there are certain challenges for clinical practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…A number of clinical studies suggested a strong correlation between exposure to environmental pollution and the incidence and mortality rates of cancer [ [16] , [17] , [18] ], which was consistent with results in animal models [ 19 , 20 ]. In addition, a series of studies have revealed that the disruption of the endocrine system plays significant roles in the development of breast cancer [ 21 ], prostate cancer [ 22 ], thyroid cancer [ 23 ], and endometrial cancer [ 24 ]. Moreover, endocrine therapy has been tried to treat these cancers mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…The oxidative damage caused by them constitutes the main mechanism for promoting carcinogenesis (Davey et al, 2007). In both breast cancer and prostate cancer, endocrine disruption can be fundamental, it can have a direct action or by binding to hormone receptors, blocking or mimicking such pathways (Corti et al, 2022;Florea & Büsselberg, 2011).…”
Section: Introductionmentioning
confidence: 99%